Zeolites Useful Minerals - Belviso, Claudia (IntechOpen, 2016)
This book collects recent results about research activities on zeolites, from synthesis to application. It is composed of two sections. The first is devoted to articles and brief review articles on the synthesis of zeolite from fly ash and final application of these newly formed minerals to solve environmental problems. The second part of the book provides useful information on different applications both of natural and synthetic zeolites ranging from environmental pollution to industrial and commercial applications. The performance of zeolite molecular sieves, hollow titanium zeolites and luminescent zeolites is interesting considering the new frontiers reached by the research on zeolites. This book is a useful instrument for researchers, teachers and students who are interested in investigating innovative aspects of the studies on zeolite.